Blends of polyacrylonitrile and lignin of sago waste for production of carbon nanofibers for removal of lead(II) from aqueous solution - Nordin, Nurul Aida (2019)
Heavy metal pollution such as lead(II) tends to cause serious environmental problems and brought toxicity effect to human and indicates that an effort must be taken in order to reduce its concentration in waste water effluents. Adsorption was proven to be economical and efficient to remove heavy metals in aqueous solution compared to other methods. There is an increasing amount of research focusing on the use of waste materials as adsorbents, aligned with the environmental protection awareness. In this study, activated carbon nanofibers (ACNFs) were produced from blends of polyacrylonitrile (PAN) and lignin of sago waste via electrospinning technique for the removal of Pb(II) ions from aqueous solution. PAN/SL ACNFs was characterized by different spectroscopic techniques and the application of PAN/SL ACNFs as the adsorbent for removal of Pb(II) ions from aqueous solution was increased three times after activation. The activation of PAN/SL ACNFs with nitric acid resulted in the attachments of oxygenated functional groups that responsible for the decreased in hydrophobicity thus promoting the metal adsorption in aqueous solution. The equilibrium time of adsorption of PAN/SL ACNFs towards Pb(II) ions was achieved in 240 mins by using 40 mg of adsorbent. The effect of initial concentration of Pb(II) was studied and the removal of Pb(II) ions from 125 mg/L solution was almost reached the monolayer coverage with the value of 555.56 mg/g. The adsorption was also dependent on the pH of the solution and the percentage removal was higher at pH 5 – 6 with 66.9 and 67.6% of Pb(II) removal. It was observed that pseudo-second order kinetic model was well-fitted with the experimental data which indicated that the adsorption process was controlled by chemisorption. The adsorption behaviour were best described by Langmuir isotherm model in which the qmax was 588.24 mg/g. From the intra- particle diffusion multilinear plot, it was suggested that two steps of adsorption were involved in the adsorption of Pb(II) ions. Therefore, in this study the adsorbent was successfully prepared from the blended of PAN and lignin of sago waste and PAN/SL ACNFs have a potential to be used as the adsorbent for the removal of Pb(II) from aqueous solution.